AKAP-9 promotes colorectal cancer development by regulating Cdc42 interacting protein 4 - Hu, Zhi-Yan (Biochim Biophys Acta, 2016)
Our previous studies have shown that PRKA kinase anchor protein 9 (AKAP-9) is involved in colorectal cancer (CRC) cell proliferation and migration in vitro. However, whether or not AKAP-9 is important for CRC development or metastasis in vivo remains unknown. In the present study, we found that AKAP-9 expression was significantly higher in human colorectal cancer tissues than the paired normal tissues. In fact, AKAP-9 level correlated with the CRC infiltrating depth and metastasis. Moreover, the higher AKAP-9 expression was associated with the lower survival rate in patients. In cultured CRC cells, knockdown of AKAP-9 inhibited cell proliferation, invasion, and migration. AKAP-9 deficiency also attenuated CRC tumor growth and metastasis in vivo. Mechanistically, AKAP-9 interacted with cdc42 interacting protein 4 (CIP4) and regulated its expression. CIP4 levels were interrelated to the AKAP-9 level in CRC cells. Functionally, AKAP-9 was essential for TGF-β1-induced epithelial-mesenchymal transition of CRC cells, and CIP4 played a critical role in mediating the function of AKAP-9. Importantly, CIP4 expression was significantly up-regulated in human CRC tissues. Taken together, our results demonstrated that AKAP-9 facilitates CRC development and metastasis via regulating CIP4-mediated epithelial-mesenchymal transition of CRC cells.